Kendala Guru dalam Pembelajaran Tematik Secara Daring (dalam Jaringan) Selama Masa Pandemi Covid 19 Di SDN 67 Kota Bengkulu - Osa Juarsa; Winda Lestari; Feri Noperman (JURIDIKDAS, 2022)
This study aims to determine the obstacles faced by teachers in online thematic learning during the Covid-19 pandemic at SDN 67 Bengkulu City. This study uses a qualitative research type. The subjects in this study were grade II A teachers, grade VI A teachers and headmaster. The object of the research was conducted at Elementary School in 67. Data collection techniques used are interviews, observation, and documentation. The results of the study show that the implementation of online thematic learning has several obstacles: 1) obstacles in preparation such as preparing online learning tools, some students do not have mobile phones, formulating learning objectives, selecting methods and media, determining time allocation and presentation of lesson plans, 2) constraints in implementation, namely from the factors of students, teachers, facilities and infrastructure, and the environment, 3) obstacles in the assessment, namely students are less active when learning takes place, lack of feedback from students, student delays when collecting assignments. It can be concluded that the solution to overcome this online learning obstacle is that the teacher is expected to establish good communication with the guardians of students in order to achieve this online learning.Keywords: Obstacles, Online Learning